2016
DOI: 10.1016/j.jcjo.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life shortly after routine cataract surgery

Abstract: ObjectiveA pilot study to explore use of a generic patient-reported outcome measure to assess patient-perceived improvements in quality of life within 2-4 weeks of routine cataract surgery, and to explore differences after first or second eye surgery. Secondary analysis explored effects of gender and ethnicity. DesignProspective observational study. ParticipantsConsecutive patients attending a weekly nurse-led postoperative clinic. MethodsThe Glasgow Benefit Inventory (GBI), a validated, post-interventional qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…14 Compared with unilateral pseudophakia, bilateral pseudophakia is associated with improved patient-reported physical and social health, improved visual acuity, and increase quality-adjusted life years. 14,15 Among our pseudophakic population, bilateral pseudophakia increased from 22% in 1988 to 60% in 2018, showing that bilateral pseudophakia has now become the predominant visual status of our residents.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…14 Compared with unilateral pseudophakia, bilateral pseudophakia is associated with improved patient-reported physical and social health, improved visual acuity, and increase quality-adjusted life years. 14,15 Among our pseudophakic population, bilateral pseudophakia increased from 22% in 1988 to 60% in 2018, showing that bilateral pseudophakia has now become the predominant visual status of our residents.…”
Section: Discussionmentioning
confidence: 93%
“…Although individuals living with pseudophakia have improved vision and an improved quality of life, an increase in the prevalence of pseudophakia also creates a need to effectively manage the long-term eyecare requirements of this growing population and to address the burden of subsequent procedures (ie, YAG capsulotomy) and complications, such as retinal tears or detachments. 14,15…”
mentioning
confidence: 99%
“…Widespread visual dysfunction reduces national economic growth, decreases productivity and increases healthcare costs [ 1 ]. Treatment of avoidable causes of blindness, especially cataract, has shown to improve quality of life, enhance overall health, alleviate poverty and elevate the economic status of a community [ 2 4 ]. The efficient implementation and evaluation of ocular health programs require population-based data on prevalence, causes of blindness and extent of ophthalmological coverage.…”
Section: Introductionmentioning
confidence: 99%
“…120,124,146,[1168][1169][1170][1171][1172][1173] Patients who had surgery in both eyes were significantly more satisfied with their visual function than patients who had surgery in only one eye. 1168,1174,1175 One study demonstrated that the cataractous eye interfered with the visual function of the pseudophakic eye and that complaints of visual disability were eliminated after second-eye surgery. 1176 Another study found that the presence of stereoacuity increased from 32% after first-eye surgery to 90% after second-eye surgery.…”
Section: Second-eye Surgerymentioning
confidence: 99%